An Access Definition and Query Language Towards a Unified Access Control Model (2013)
In this work we suggest a meta access control model emulating established access control models by configuration and offering enhanced features like the delegation of rights, ego-centered roles, and decentralized administration. The suggested meta access control model is named ''Access Definition and Query Language'' (ADQL). ADQL is represented by a formal, context-free grammar allowing to express the targeted access control model, policies, facts, and access queries as a formal language.